Hospitalization for asthma attacks in children: What is the cause? Case and control study - Recabarren Lozada, Arturo (2021)
Objective: To determine the clinical, laboratory and epidemiological factors that motivate hospitalization for asthmatic crisis at Yanahuara Hospital, Arequipa-Peru. Material and methods: Observational, prospective, case-control study in which risk factors for hospitalization were studied, comparing 84 hospitalized asthmatic children with 110 control children of the Asthma Program. Results: The highest frequency of hospitalization occurs in the range of 6-12 year-old (51.2 %) majority male (56 %). The associated clinical factors were the fact of presenting previous respiratory symptoms (p<0.01), history of allergic rhinitis (p<0.01; OR=3.80) and history of exercise intolerance (EIB) (p<0.01; OR=4.89). Among the laboratory factors, high IgE was found positive for age (p=0.037; OR=2.70). The epidemiological factors that were associated with asthmatic crisis were the history of having parents with asthma (p=0.008; OR=1.59), previous viral respiratory infection (p<0.01; OR=27.61), recent exposure to animal dandruff (p=0.006; OR=2.52), exposure to cigarette smoke at home (p=0.003; OR=5.94), increased attention in Emergency before the attacks (p<0.01; OR=29.73), do not use inhaled corticosteroids for disease management (p<0.0; OR=140.25), excess use of rescue medication (B2 agonists) (p<0.01; OR=57.14) and finally inadequate use of the inhalation technique (p<0.01; OR=11.71). Conclusion: This study shows that there are several factors associated with hospitalization due to asthma attacks and that can be easily controlled and potentially modified to reduce hospital admissions and asthma care costs.